2-Adamantylidene and its heavier analogues: hyperconjugation versus lone pair stability and electrophilicity versus nucleophilicity1. Issue 10 (14th March 2015) - Nijesh, Karikkeeriyil; Rojisha, Vallyanga Chalil; De, Susmita; Parameswaran, Pattiyil
<x xml:space="preserve">Abstract</x> Too heavy to bend: The Cieplak-type hyperconjugative interaction mainly contributes to the stability of 2C and 2Si whereas the inertness of lone pairs is the major factor for 2Ge and 2Sn. These molecules (2X; X = C–Sn) can be classified as a class of ambiphilic compounds.